Effect of foaming agents on process conditions, characteristics, and stability of foam-mat freeze-dried pandan (Pandanus amaryllifolius) powder - Saowaratcharee Rin-ut (2020)
© 2020 Wiley Periodicals LLC. Foam-mat freeze-drying (F-FD) of aqueous pandan extract with various foaming agents (egg white protein, sodium caseinate, and METHOCEL) was carried out to improve the process conditions, physicochemical properties, and stability of pandan powder. The foamed pandan solution with egg white protein (F-EW) provided the most stable foam structure and shortened drying time to 6 hr, while the control took 24 hr to dry at the same sample thickness. The F-EW freeze-dried pandan powder (FDPP) had the highest hue angle, the highest greenness (a* value), the lowest bulk density, and high solubility. The reaction rate constants for the physicochemical changes in foamed-freeze-dried pandan powders were lower than those of the control and the highest color stability was recorded for F-EW FDPP when stored at high temperature (37°C) for 12 weeks. Egg white at a concentration of 10% w/w is an appropriate foaming agent for producing pandan powder via the F-FD. Practical applications: Natural pandan leaf extract is a commercially available product nowadays both in concentrate and powder form. Functional ingredients are offered to the health-conscious consumers, such as natural pandan powder with prebiotic. Foam-mat freeze-dried pandan powder with various types of foaming agents, such as egg white protein, sodium caseinate, and METHOCEL may be the new alternative technology for the production of functional ingredients which not only use as a natural food colorant and flavor but also as the foaming aid agent in foam-type food products.